2012
DOI: 10.1002/ceat.201100251
|View full text |Cite
|
Sign up to set email alerts
|

Selective Extraction of Lutein from Alcohol Treated Chlorella vulgaris by Supercritical CO2

Abstract: A pretreatment process using alcohol for the removal of chlorophyll a, b and b-carotene from Chlorella vulgaris was developed to improve the yield and selectivity of lutein in the extract obtained by supercritical carbon dioxide extraction. Supercritical carbon dioxide extraction was carried out after pretreatment in the pressure range of 20 to 40 MPa and the temperature range of 40 to 80°C. Ethanol and methanol were selected as elution solvents, of which ethanol was found most suitable for the elution, or pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 20 publications
2
37
0
Order By: Relevance
“…In the present work, supercritical carbon dioxide (SCCO2) was employed as a solvent extraction [10][11][12][13][14] to extract phenolic compounds from grains of paradise seeds. The SCCO2 extraction technique is very advantageous and environmentally friendly compared with other conventional extraction technique, such as soxhlet extraction technique.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, supercritical carbon dioxide (SCCO2) was employed as a solvent extraction [10][11][12][13][14] to extract phenolic compounds from grains of paradise seeds. The SCCO2 extraction technique is very advantageous and environmentally friendly compared with other conventional extraction technique, such as soxhlet extraction technique.…”
Section: Introductionmentioning
confidence: 99%
“…There are two main procedures by which co-solvents or modifiers can be incorporated in the SFE process: by either mixing of the modifier with the CO 2 flow or by mixing the modifier with the raw material in the extraction cell. In a work done in our group (Ruen-ngam et al 2012), the use of ethanol as co-solvent with CO 2 increased the extraction yield of astaxanthin extract by rupturing the solute/ solid matrix interactions, and substituting co-solvent molecules in the solid active sites. Machmudah et al (2006) also showed that ethanol concentration increased the astaxanthin content of the extracts from micro-algae due to increased carotenoid-alcohol interactions which increase the solvating power of CO 2 .…”
Section: Effect Of Co-solvent Modifiermentioning
confidence: 98%
“…In many cases, SFE has been found to be a superior technique for the extraction of heat sensitive carotenoids. A number of investigations are available to describe several SFE issues, such as the effect of temperature, pressure, co-solvents, solvent flow rate [19,106] and pretreatment, the extraction of carotenoids, selectivity [107], kinetics [29,107,108], and the modelling of extraction [26,109]. …”
Section: Nonconventional Extraction Of Carotenoidsmentioning
confidence: 99%
“…In some instances, high CO 2 pressure (>400 bar) has caused lower recovery of carotenoids [108,112], and on the other hand, some researchers have observed a reduction in carotenoid yields at low CO 2 pressure, the latter dependent on the temperature used [107,113]. Pressure has contrasting effects on the extraction yield; increasing pressure (at a constant temperature) increases the density of CO 2 , and consequently, the solvation power of the fluids, which in turn increases the solubility of the compounds and extraction yield.…”
Section: Nonconventional Extraction Of Carotenoidsmentioning
confidence: 99%